Metafora Maknawi: Pada Kata Al-Zhulumat dan Al-Nur dalam Kitab Tafsir Mafatih Al-Ghaib Karya Fakhruddin Al-Razi - Diki Saputra Siregar; Rizky Rahakim Harahap; Mus’ab Marbun (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this exploration is to recognize the enormous use of representation in the first verse of the Al-Qur'an Surah Ibrahim, especially the words Al-Zhulumat and Al-Nur. The main point is to interpret the task of isti'arah in giving an uncertain meaning to a part which can give rise to various translations. Using a scientific-rational approach, this research method examines the text of the Al-Qur'an through language and literature studies, with a focus on metaphors, especially relevant metaphors. This research approach is qualitative, with data collection using the Library Research method (library research). This investigation also includes interpretive efforts to better understand how isti'arah can be used as a tool of understanding, namely the translation of Fahruddin Al-Razi's Mafatih Al Ghaib. Findings (1). The study involved various translations resulting from the ideas of Intisari and Majaz in the application of isti'arah (2). Fakhruddin Al-Razi underlined that isti'arah helps Muslims understand the Al-Qur'an by explaining the meaning of complex verses, especially the terms Al-Zhulumat and Al-Nur in Surah Ibrahim verse 1. Apart from that, this study also functions as a reminder the idea of ​​content 'direction, which is not mentioned in the language of scholars but is present in the disciplines of tafsir and the Koran. Therefore, this research takes a dogmatic-ideological approach in studying the Koran while allowing for a rational-scientific approach.